Dispositionsprincipen - Principens tillämpning i skiljeförfaranden med ett särskilt fokus på tillämpningen i Svea Hovrätts mål nr T 3623-21 och T 1356-18 - Kouthoofd Muldin,Cesar (2023)
The principle of party-disposition is a fundamental principle in Swedish pro-cedural law. The principle means that the court should only undertake a cer-tain procedural action upon the request of one or both parties. This principle applies to both court proceedings and arbitration disputes. In Swedish pro-cedural law, the principle of party-disposition is primarily expressed in Chapter 17, Section 3 of the Code of Judicial Procedure, which states in the first sentence that a judgment may not be rendered for more or other than what the party has claimed, and in the second sentence that a judgment may not be based on a circumstance that the party has not invoked in support of their claim. Although the provision in Chapter 17, Section 3 of the Code of Judicial Procedure is not directly applicable to arbitration disputes, it has legal signif-icance as an expression of the principle of party-disposition in arbitration as well. This thesis examines the scope and application of the principle of par-ty-disposition in arbitration proceedings. The thesis also compares how the principle of party-disposition may differ in ordinary court proceedings and arbitration proceedings. The main focus of the thesis is to investigate how the principle of party-disposition is applied in arbitration proceedings. This investigation is carried out by analyzing several challenge judgments from the Svea Court of Ap-peal. A challenge to an arbitration award cannot be based on substantive grounds. However, it can be based on procedural grounds. The most com-monly invoked ground for challenge under the Swedish Arbitration Act (LSF) is Section 34, paragraph 1, subparagraph 3, which pertains to exceed-ing the scope of the arbitrators' mandate. This ground for challenge is con-sidered to be a consequence of the principle of party-disposition. To investi-gate the impact of the principle of disposition on arbitration proceedings, several challenge judgments have been examined and analyzed. In November 2022, the Svea Court of Appeal set aside two arbitration awards, as it assessed that the arbitrators had departed from the principle of disposition and thereby exceeded their mandates in a way that likely affect-ed the outcome. In case no. T 1356-18, the arbitral tribunal had awarded costs that were not requested by the party making the application, based its judgment on circumstances that were not invoked, and failed to decide on a prescription issue raised in the case. In the other case, case no. T 3623-21, the Court of Appeal set aside the arbitration award because the arbitral tri-bunal's decision did not correspond to the claims made by the party making the application. These cases confirm the significance of the principle of par-ty-disposition in arbitration proceedings, and it is evident that analogies from the procedural framework of the Code of Judicial Procedure are used in arbitration proceedings.
Keywords: Civilrätt; Skiljemannarätt; Civilprocess; dispositionsprincipen